Faktor-Faktor yang Berhubungan dengan Tingkat Depresi pada Lansia yang Tinggal di Rumah Pelayanan Sosial - Maya Audita Nurhayati; Iskim Luthfa; Moch. Aspihan (Journal of Health, Medical, and Psychological Studies, 2026)
Depression is a common mental health issue among older adults, particularly those living in social care facilities due to limited social support, declining physical function, and reduced independence. These factors can adversely affect quality of life and increase the risk of physical and psychological complications. This study employed a cross-sectional design with 135 elderly respondents residing in Pucang Gading Social Care Home and Wening Wardoyo Home. A total sampling technique was used. Data were collected using demographic questionnaires, the Multidimensional Scale of Perceived Social Support (MSPSS), a chronic disease questionnaire, the Barthel Index, and the Geriatric Depression Scale (GDS-15). Data analysis included univariate, bivariate using Spearman’s test, and multivariate analysis using logistic regression. Most respondents were aged 60–74 years (63.0%) and female (63.0%). Spearman’s test indicated significant correlations between social support (p=0.000) and independence (p=0.000) with depression levels. Chronic diseases showed a significant but very weak relationship (p=0.034). Multivariate analysis identified social support as the most dominant factor associated with depression (p=0.002). Conclusion social support and independence are significantly associated with depression levels among older adults living in social care homes, with social support emerging as the most influential factor